PENGARUH FITUR DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI (STUDI KASUS PADA KOMUNITAS FACEBOOK MI FANS KARAWANG) - Andrian Nur Aziz (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and explain the level of Purchase Decisions on Xiaomi smartphones based on Product Features and Brand Image on members of the Mi Fans Karawang Facebook community. This research was conducted through a statistical technique approach using SPSS 24, data collection using incidental sampling technique on 362 respondents with research subjects being members of the Mi Fans Karawang facebook community. Before testing the hypothesis, in this study, the validity of the data was tested. The data analysis technique used is the scale range analysis technique and path analysis. The results of this study reveal that Product Features on Xiaomi smartphones are in the agreed criteria, meaning that Product Features on Xiaomi smartphones can be well received by consumers. Furthermore, the Brand Image on Xiaomi smartphones is in the agreed criteria, meaning that the Xiaomi smartphone brand image can be well received by consumers. Then, the Purchase Decision on the Xiaomi smartphone is on the agreed criteria, meaning that the Purchase Decision on the Xiaomi smartphone can be accepted by consumers. There is a moderate and unidirectional positive correlation between Product Features and Brand Image Quality. Partially Product Features have a positive and significant effect on Purchase Decisions. While the brand image also has a positive and significant effect on purchasing decisions. Product Features and Brand Image have a Positive and significant effect on Purchase Decisions on Xiaomi smartphones (a case study on the Mi Fans Karawang facebook community)